Estudo sistemático de um repositório institucional: o caso da Universidade Federal do Pará - CHUCRE, William Silva (2018)
The study focused on an investigation of institutional repositories and their influence on the scientific community. Because of this, it is important to reflect on the importance of the role of universities in student training. The professional must reinforce his qualities and knowledge, as well as discern what technological resources available to use the repositories; acquire security in using digital content; and get guidance on research to enrich their knowledge. From this analysis it was possible to perceive the importance of the democratization of information in the university field, the discussion about how to allow free access to the academic community or the public in general. The method of how to contribute to research for better dissemination is still a great challenge for researchers. Finally, through the entire study, it was possible to confirm that institutional repositories play an important role in promoting greater visibility for institutions. They can help and empower scientific research for a more solid and comprehensive perspective.